MODEL SELF ORGANIZED LEARNING ENVIRONMENTS (SOLE) DAPAT MENINGKATKAN KREATIVITAS PADA PELAJARAN KIMIA - Maya Mutiasari (Universitas Muhammadiyah Pontianak, 2021)
Learning during the covid-19 pandemic requires adjustments, due to the implementation of the Circular Letter of the Ministry of Education and Culture number 4 of 2020 which makes teachers and students unable to meet directly to carry out the learning process but by conducting distance learning (PJJ). Distance learning (PJJ) can take place well, it requires a learning model that is in accordance with the material to be studied, so that students can learn well and remain creative. The purpose of this study is to determine the success rate of implementing the model Self Organized Learning Environments (SOLE) in distance learning, so that it can make students more creative in the application of Gay Lussac's law in everyday. This study uses method best practice with the steps of the SOLE model activity which has three stages of activity, namely asking questions, investigating and reviewing. Assessment is carried out to assess aspects of knowledge, skills and attitude assessment. From the results of the questionnaire, it was found that the Self Organized Learning Environments (SOLE) model was pleasant for 95% of students, increasing students' understanding of the material, which was 78.62%. Meanwhile, from the skill assessment, most of the students have been able to do the practicum well. From the results of the research that has been done, it can be concluded that there is an increase in the creativity of students in chemistry lessons.